Ekstrak air daun Ceplikan (Ruellia tuberosa L) berpengaruh terhadap kadar SGOT, SGPT dan gambaran histologis hepar tikus DM - Fitri Ardiani; Wiryatun Lestariana; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2011)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder as indicated by hiperglycemia caused by insulin defciency produced by pancreatic islet ß cell which triggers metabolic disorder of carbohydrate, protein and fat, and tends to cause complications. One of the complications is liver damage caused by DM which is probably due to lipid peroxydation, subsequent to free radical production. The common biochemistry signs of liver damage are increasing activities of some enzym such as transaminase pyruvat glutamate serum in the blood. Ruellia tuberosa L is a traditional plant and used by people as diabetic traditional drug. Flavonoid, saponin, zink as antioxidant can decreased of blood glucose in diabetic.Objective: The study aimed to identify the effect of Ruellia tuberosa L extract on glutamate oxaloacetate and glutamate pyruvat transaminases as well as liver histology of diabetic white mice (Rattus norvegicus).Method: The study was pure experimental that used a pre-post test control group design. The study used 30 male Rattus norvegicus. They were divided into 5 groups, each group consisting of 6 rats. Group I rats served as the normal control. Groups II to V consisted of rats with DM induced with alloxan 170 mg/kgBB subcutaneously. The experiment made was as followed. Group I served as control, group II was DM+aquades, group III was DM+Ruellia tuberosa L extract 1.6 mg/ kgBB/day, group IV was DM+Ruellia tuberosa L extract 3.2 mg/kgBB/day, and group V was DM+Ruellia tuberosa L extract 6.4 mg/kgBB/day. Glutamate oxaloacetate and glutamate pyruvat transaminases was measured before beginning and end of the treatment. The blood was taken from sinus orbitalis. At day 30 (end of the study) the rats were sacrifced for their liver. Data of transaminase oxaloacetate glutamate serum and transaminase pyruvat glutamate serum level were analyzed using one way ANOVA. The result of liver histology was analyzed descriptively.Results: The effect of Ruellia tuberosa L extract within 30 days of study could minimize level of transaminase oxaloacetate glutamate serum and transaminase pyruvat glutamate serum of DM rats. Maximal decreasing in extract 3,2 mg. Histologically there was no damage of the liver.Conclusion: Ruellia tuberose L extract could minimize level of transaminase oxaloacetat glutamate serum and transaminase pyruvat glutamate serum of DM and liver histology is normal.